Age-related distribution of cells in cell cycle phases in dependence on specific rate of growth in chemostat cultures of Candida utilis - Vraná, D (Folia microbiologica, 1992)
Individual cells in chemostat cultures of Candida utilis (D = 0.05, 0.1, 0.2, 0.25, 0.3 and 35/h) were analyzed according to the number of bud scars and according to their position in the cell cycle. The distribution in the cell cycle phases depends both on the genealogical age and the specific rate of growth.
Keywords: buněčný cyklus; časové faktory; Time Factors; Candida; mykologie; Mycology; Cell Cycle